2014
DOI: 10.1111/bju.12508
|View full text |Cite
|
Sign up to set email alerts
|

Extent of lymph node dissection at nephrectomy affects cancer‐specific survival and metastatic progression in specific sub‐categories of patients with renal cell carcinoma (RCC)

Abstract: Objective• To test whether the number of lymph nodes removed affects cancer-specific survival (CSS) or metastatic progression-free survival (MPFS) in different renal cell carcinoma (RCC) scenarios. Methods• We used Cox regression analyses to analyse the effect of the number of lymph nodes removed on CSS and MPFS in 1983 patients with RCC treated with nephrectomy.• To adjust for possible clinical and surgical selection bias, analyses were further adjusted for number of positive nodes, presence of metastases, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 20 publications
1
54
1
Order By: Relevance
“…Similarly, in another non-randomized retrospective study, Pantuck et al [11] [20,32]. For instance, Capitanio et al [20] did not find any correlation between the number of nodes removed and cancer-specific mortality in patients with metastases at diagnosis, unless the patient had one of the previous above-cited unfavorable characteristics. More recent data from Memorial Sloan-Kettering Cancer Center on 258 metastatic patients treated with cytoreductive nephrectomy showed similar cancer control in patients treated with different lymph node templates (hilar vs. other) or different number of nodes removed (0-3, 4-7 or ≥8) [32].…”
Section: Metastatic Patients (Cm1)mentioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, in another non-randomized retrospective study, Pantuck et al [11] [20,32]. For instance, Capitanio et al [20] did not find any correlation between the number of nodes removed and cancer-specific mortality in patients with metastases at diagnosis, unless the patient had one of the previous above-cited unfavorable characteristics. More recent data from Memorial Sloan-Kettering Cancer Center on 258 metastatic patients treated with cytoreductive nephrectomy showed similar cancer control in patients treated with different lymph node templates (hilar vs. other) or different number of nodes removed (0-3, 4-7 or ≥8) [32].…”
Section: Metastatic Patients (Cm1)mentioning
confidence: 94%
“…Similarly, in another previously cited study, the number of nodes removed showed an independent, protective effect on CSS also in patients with pT3c-pT4 RCC (HR 0.89, p < 0.001). The removal of each additional lymph node was associated with roughly a 10 % increase in CSS and metastatic progression-free survival [20].…”
Section: Locally Advanced Disease (Ct3-t4)mentioning
confidence: 97%
See 3 more Smart Citations